TINJAUAN YURIDIS TENTANG PEMBULLYAN TERHADAP ANAK AUTIS (Studi Kasus Putusan Pengadilan Negeri Pangkajene Nomor 83/Pid.Sus/2020/PN Pkj) (Qawanin Jurnal Ilmu Hukum, 2021)
This study aims to determine and analyze the application of the law regarding bullying of children with autism and to analyze judges' legal considerations in cases of bullying of children with autism. The research method used in writing this thesis is a normative method, with secondary and primary data coverage, this research was conducted at the Pangkajene District Court. The results of this study indicate that based on Article 80 paragraph (1) Jo. Article 76 C of Republic of Indonesia Law Number 35 of 2014 concerning amendments to Law of the Republic of Indonesia Number 23 of 2002 concerning Child Protection and Law Number 8 of 1981 concerning Criminal Procedure Law and other relevant laws and regulations, are in accordance with the implementation law by the judge in relation to the case of child bullying. It is hoped that this research recommendation from the court and legal practitioners to be able to improve themselves and then return to the corridor line that has been mandated by the state and the law.